1986
DOI: 10.1002/mus.880090203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on the motor unit

Abstract: The motoneuron part of this review deals with the changes in recruitment and firing rates of the motor unit types upon changes from a physically inactive life to endurance or strength training. The muscle fibers react to prolonged exercise by adaptation to a higher level of performance. A matter of discussion is the prerequisites for a transformation between the basic muscle fiber types, slow twitch and fast twitch, during voluntary (transsynaptic) activity, which is demonstrated after artificial nerve stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(41 citation statements)
references
References 257 publications
0
38
0
3
Order By: Relevance
“…Indeed, it has been shown that an increase in muscle strength results in more effective recruitment of motor units as well as increased cross-sectional area of the muscle. 24,25 In addition, exercise induces an increase of muscle capillary density with decreased mitochondrial density and lipid storage. Exercise has also been shown to induce neural changes, including, increased activation, increased motor synchronization, and cross-transference of strength between limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that an increase in muscle strength results in more effective recruitment of motor units as well as increased cross-sectional area of the muscle. 24,25 In addition, exercise induces an increase of muscle capillary density with decreased mitochondrial density and lipid storage. Exercise has also been shown to induce neural changes, including, increased activation, increased motor synchronization, and cross-transference of strength between limbs.…”
Section: Discussionmentioning
confidence: 99%
“…225,227 The specific effect of NMES-facilitated exercise on the motor unit has been reviewed. 91 Numerous skeletal-muscle biochemical and physiological adaptations are induced by chronic low-frequency electrical stimulation in an animal model. 189 Fast to slow twitch alterations of muscle fibers are associated with alterations of calcium dynamics and myofibrillar proteins; white to red fiber transformations are associated with changes in mitochondrial enzymes, myoglobin, and the induction of angiogenesis.…”
Section: Other Therapeutic Applicationsmentioning
confidence: 99%
“…Therefore, in the present study, an exercise program involving hind limb movement similar to a bicycling motion was utilized to determine the potential influence on muscle size and MyHC expression following SCI. 15,34,45,47 …”
mentioning
confidence: 98%